2017
DOI: 10.1038/s41467-017-00294-0
|View full text |Cite
|
Sign up to set email alerts
|

Lyn and Fyn function as molecular switches that control immunoreceptors to direct homeostasis or inflammation

Abstract: Immunoreceptors can transduce either inhibitory or activatory signals depending on ligand avidity and phosphorylation status, which is modulated by the protein kinases Lyn and Fyn. Here we show that Lyn and Fyn control immune receptor signaling status. SHP-1 tyrosine 536 phosphorylation by Lyn activates the phosphatase promoting inhibitory signaling through the immunoreceptor. By contrast, Fyn-dependent phosphorylation of SHP-1 serine 591 inactivates the phosphatase, enabling activatory immunoreceptor signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 49 publications
6
83
1
1
Order By: Relevance
“…However, data from SLE patients have shown them to have lower levels of Lyn compared to healthy controls, implying that lower levels may be associated with disease . In addition, studies in B cell lines show that Lyn is required for inhibitory signals in response to weak BCR crosslinking . Lyn –/– mice are susceptible to an inducible immune complex–mediated nephritis as well as to antibody‐induced arthritis .…”
Section: Variants Affecting B Cell Signaling Molecules Affect Both Pementioning
confidence: 99%
See 1 more Smart Citation
“…However, data from SLE patients have shown them to have lower levels of Lyn compared to healthy controls, implying that lower levels may be associated with disease . In addition, studies in B cell lines show that Lyn is required for inhibitory signals in response to weak BCR crosslinking . Lyn –/– mice are susceptible to an inducible immune complex–mediated nephritis as well as to antibody‐induced arthritis .…”
Section: Variants Affecting B Cell Signaling Molecules Affect Both Pementioning
confidence: 99%
“…In addition, studies in B cell lines show that Lyn is required for inhibitory signals in response to weak BCR crosslinking . Lyn –/– mice are susceptible to an inducible immune complex–mediated nephritis as well as to antibody‐induced arthritis .…”
Section: Variants Affecting B Cell Signaling Molecules Affect Both Pementioning
confidence: 99%
“…Susceptibility to rapid, activation-induced degradation differentiates LynA from the splice variant LynB and the other macrophage SFKs. Hck, Fgr, LynB, and Fyn (17, 19), are degraded >10-fold more slowly than LynA during 3-IB-PP1 treatment (20) (Figure 2A) . Although not expressed in macrophages, Lck is also degraded more slowly than LynA (Figure 2B) .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mechanisms work together to tune the responsiveness of macrophages and other myeloid cells, including negative regulation by the phosphatases CD45 and CD148 (5, 9, 10), cytoskeletal barriers to diffusion (11), signaling via immunoreceptor tyrosine inhibitory motifs (ITIMs) (12) and inhibitory ITAMs (13, 14), and degradation and mislocalization of signaling molecules targeted for polyubiquitination by ubiquitin ligases (15, 16). The SFKs, which in myeloid cells typically include Fgr, Fyn, and two splice forms each of Hck and Lyn, may also have positive and negative functions (12, 1719). Layered onto the traditional positive-and negative-regulatory roles of the SFKs, we have shown that activated LynA (the longer of the two Lyn splice forms) is rapidly and specifically targeted for polyubiquitination and degradation, forming the basis of a signaling checkpoint that blocks spurious macrophage activation (20).…”
Section: Introductionmentioning
confidence: 99%
“…7A-C). In addition, we assessed phosphorylation of SHP-1 on S591, a posttranslational modification induced by PKC and that has been linked to the reduction of phosphatase activity of SHP-1 (39,40), and did not observe any difference under conditions of TAOK3 deficiency.…”
Section: Taok3 Deficiency Is Associated With Enhanced Interaction Betmentioning
confidence: 99%